Medicinal Plant Species in Lakuan Buol Village, Lakea District, Buol Regency, as Learning Media - Wahyu Indah Septiani; Gamar B. N. Shamdas; Vita Indri Febriani; Lestari M. P. Alibasyah; Aan Febriawan; Musdalifah Nurdin (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aims to identify medicinal plant species, describe the plant parts used and their processing methods, and develop learning media in the form of a pocket book and flipbook in Lakuan Village, Lakea Sub-district, Buol Regency. This research used a descriptive qualitative approach through field observations, interviews with key informants (traditional healers) and supporting informants (medicinal plant users), as well as documentation. Data were analyzed descriptively by grouping plant species, used parts, and processing techniques, supported by literature review. The results showed 32 species from 24 families, with specific plant parts used, namely leaves for fever and wounds due to their ease of processing, roots for internal diseases, rhizomes as anti-inflammatory and antibacterial agents, stems for relaxation, fruits for digestion and immunity, and flowers for cough treatment. The pocket book and flipbook media were chosen because they are practical, concise, and interactive, making it easier for students to understand the material. The feasibility test results indicated that the media was categorized as highly feasible as a context-based learning resource.